Seashore Paspalum Management for Home Lawn Use in Florida - Laurie E. Trenholm; Joseph Bryan Unruh (EDIS)
While seashore paspalum generally does very well under professional management on golf courses or athletic fields, lack of knowledge on how to properly manage the grass in the home lawn environment may result in problems. Management of seashore paspalum differs from that for most other warm-season grasses in some key areas. These include: fertilization, mowing, irrigation, herbicides , insect and disease problems, and establishment requirements. This document is ENH 897, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date June, 2003.